The Capston Project as a means to improve the quality of assessment within the teaching practice area: A proposal by the Universitat Internacional de Catalunya - M. Teresa Fuertes Camacho; M. Carmen Balaguer Fàbregas (Universitat Politècnica de València, 2012)
The evaluation of educational practices is, in general, a systematic process that revolves around the axis tutor school, tutor college practices and students' self-assessment. The subjective perceptions and the personal bonds that are established and the inability to visualize in a continuous manner how students manage their educational practice can lead to some biases in the objectivity required for any evaluation. These biases affect the quality of our assessments. This article attempts to provide arguments to support the value of the Capstone Project, included in the Practicum module, as a confirmation of the personal educational competence. At the same time this model provides a proposal for the assessment of the project, based on the organization of the tasks that students, tutors and university tutors have to carry out, including, in this case, the members of the Assessment Jury. The benchmark of our evaluation is set by the competences described in the regulations of the Faculty of Education at the Universitat Internacional de Catalunya, reformulated as learning outcomes. In conclusion, it aims to adapt the observation and assessment of the teaching-practice behaviours to a set of indicators or items as specific as possible and contextualized to different educational realities. And with regard to the Capstone Work we intend to use the same criteria, but focusing on the professionalizing aspects of entrepreneurial spirit, creativity and decision making.